PROFIL PASIEN TUBERCULOSIS MULTIDRUG RESISTANCE (TB-MDR) DI POLIKLINIK TB-MDR RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE APRIL 2013-JUNI 2014 - Vivin Anggia Putri; Indra Yovi Yovi; Dina Fauzia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTMultidrug Resistance Tuberculosis (MDR-TB) is Mycobacteriumtuberculosis resistance to at least two types of first-line OAT which are rifampicinand isoniazide. There were 6900 cases of MDR-TB at Indonesia in 2012. MDRTBcause limitation to TB's control programs. The identification of patient'scharacteristics and the affecting factor of MDR-TB occurence was expected toincrease the succes rate of TB treatment and prevent MDR-TB. This was adescriptive study with cross sectional approach by using patient's medical recordsand guided interview for MDR-TB patients in the MDR-TB clinic at ArifinAchmad Hospital in Riau Province Period April 2013 - June 2014. Samplecollected by using total sampling method. The results that was obtained from 18patients with MDR-TB, the largest distribution of age group was 24-44 years(50%). The most common gender was male (66.7%), the majority of MDR-TBpatients have less nutritional status (61.1%) and most patients experiencing oldcough (77.8%). Most patients with pulmonary TB type that was the type of relapsecases (83.3%), the most anti drug resistance tuberculosis were rifampicin andisoniazide (50%) and the treatment regimen of patients with MDR-TB that wasoften used is the Z-E-Km-LFX-Eto-Cs (61.1%). Side effects from the previoustreatment and comorbid DM patients were identified as patient's factors, mostpatients did not get education by doctors about the treatment of MDR-TB before,the far distance from patient's home to health facilities and communication withhealth care providers in the previous treatment also indentified as factors ofprogram and health system.Keywords : Tuberculosis, MDR-TB